Pengaruh Word Of Mouth dan Kualitas Pelayanan Kredit Terhadap Profit Koperasi Serba Usaha Mitra Rakyat Kantor Cabang Betro Juanda - Erlinda Yulia Damayanti; Hery Pudjoprastyono (Widya Manajemen, 2022)
The economy is an important thing for human survival, because basically the economy is the main spear of human activity. In carrying out economic activities, humans also need activities that support these economic activities, including services from financial institutions and financial institutions such as banking services and cooperatives. In this study, it uses Explanative Quantitative Research where in this explanative quantitative research it produces accurate data from the right calculations. The data collection method in this study was carried out by distributing questionnaires to 94 customers of KSU Mitra Rakyat who became customers in 2016-2020. In this study to analyze the data, the author uses the PLS technique. Word of mouth can have a significant positive effect on increasing profits at KSU Mitra Rakyat. This proves that Word of Mouth affects the increase. Quality of Credit Services has a significant positive effect on increasing profits at KSU Mitra Rakyat. The better the quality of credit services used, the higher the profit at KSU Mitra Rakyat. From the results of the research that has been done, the company must maintain recommendations, physical evidence and empathy. Furthermore, it must be further improved, in order to achieve the desired profit of the company.